(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Intravenous Dexmedetomidine is associated with stable cardiovascular profile and less associated withfear, anxiety and agitation. Spinal anesthesia (SA) offers many advantages over general anesthesia, likeproviding analgesia and muscle relaxation in a conscious and compliant patient and an uneventfulpostoperative recovery. But retained consciousness during surgery or patient awake causes fear, anxietyin perioperative period. The fear of surgery, the unfamiliar environment of operation room, the sight andsounds of sophisticated instruments, and the masked faces makes the patient panic. The intense sensoryand motor block, continuous supine position and the inability to move the body also brings a feeling ofdiscomfort and phobia in many patients. Thus, adequate sedation and control of stress, pain, fear andpatient satisfaction are essential components during anesthesia. Sedation has been shown to increasepatient satisfaction during regional anesthesia. I conclude that, during spinal anesthesia, IVsupplementation of dexmedetomidine is more effective than midazolam infusion, as it provides longerduration of sensory and motor blockade and postoperative analgesia with minimal and similar sideeffects. It provides satisfactory arousable sedation without respiratory depression. Haemodynamic changesobserved in our patients were very small and could be ignored. Patient remained stable haemodynamicallythroughout the intra-operative period. So dexmedetomidine seems to be a good choice for sedation inspinal anesthesia (SA). JBSA 2020; 33(2): 92-97